2019
DOI: 10.1080/04250494.2019.1688657
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual communication under the radar: how multilingual children challenge the dominant monolingual discourse in a super-diverse, Early Years educational setting in England

Abstract: The operant "one nationone language" model in Western culture has resulted in linguistic hegemony being almost universally presented as an uncontentious reality. This article accepts Foucault's challenge to deconstruct this officially sanctioned "truth" by looking at how the educational system in England legitimises the discourse that speaking English is normal, marginalising multilingual practices. Data is drawn from a year-long study of thirty "superdiverse" children in an inner-city school in the north of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…There were several occasions throughout the research when I documented children speaking languages that had not been revealed by any other source of data collection, and were only brought to light as a result of the discussion of the comic depicting the event. This led to the construction of a theme around ‘concealing home languages' (Fashanu et al, 2019), highlighting the fact that children actively choose to ‘claim, downplay or simply ignore ethnic affiliations’ according to the situation (Huber and Spyrou, 2012: 299). The children’s concealment of home languages was pertinent to the overarching research that aimed to better understand how the intersections between different socio-cultural contexts contribute to children’s multimodal communicative practices within a super-diverse environment.…”
Section: Making Snailsmentioning
confidence: 99%
“…There were several occasions throughout the research when I documented children speaking languages that had not been revealed by any other source of data collection, and were only brought to light as a result of the discussion of the comic depicting the event. This led to the construction of a theme around ‘concealing home languages' (Fashanu et al, 2019), highlighting the fact that children actively choose to ‘claim, downplay or simply ignore ethnic affiliations’ according to the situation (Huber and Spyrou, 2012: 299). The children’s concealment of home languages was pertinent to the overarching research that aimed to better understand how the intersections between different socio-cultural contexts contribute to children’s multimodal communicative practices within a super-diverse environment.…”
Section: Making Snailsmentioning
confidence: 99%
“…In recent research into multilingual communication, Fashanu et al (2020) build on research that reveals how young children create their own cultures and use multiple strategies to assert agency through sociodramatic play, silence and negotiation (ibid: 97). These researchers also uncover children's use of space as 'a key theme that is frequently found within the literature on children's agency and resistance to discipline' (ibid: 97).…”
Section: Siblings As Agentive In Bi-and Multilingual Familiesmentioning
confidence: 99%
“…Teaching methods that draw upon creative inquiry also afford opportunities to challenge monolingualist assumptions in primary education. Fashanu, Wood, and Payne (2020), for example, use a 'language portraits' technique (Busch 2018) to explore multilingual primary school pupils' communicative repertoires, redolent of Katerina's flying horse drawing. Hohti (2016, 87) stresses the importance of 'listen [ing] to those voices that usually do not get heard' .…”
Section: Extract 10 Interview With Mother 03/11/2016mentioning
confidence: 99%